Study on the Stability of Slopes Reinforced by Composite Vegetation Combined with a Geogrid under Rainfall Conditions - Qizhi Hu; Yong Zhou; Gaoliang Tao (Advances in Civil Engineering)
The planting of shrubs and trees on geogrid-reinforced slopes is an important ecological slope protection method that is frequently implemented in the rainy areas of southern China. First, this paper analyzes the soil-fixing principle of the geogrid and root system and demonstrates the feasibility of using composite vegetation of shrubs and trees to reinforce the slope with a geogrid. Using the Yushi Expressway project in Guizhou, we conducted a stability analysis of slopes under different working conditions and different reinforcement modes. We determined that the ecological protection method of combining composite vegetation with a geogrid can effectively increase the stability of slopes. The maximum displacement of the ecological slope under rainfall conditions was reduced by 82% compared with the original slope, and the overall stability was improved by 35%. Four factors affect the slope stability: the depth of shrub reinforcement, depth of anchorage of trees, distribution of trees, and spacing of the geogrids. An orthogonal analysis considering these 4 factors with 3 levels was implemented. The following optimal combination was obtained to ensure ecological protection under rainfall conditions: a shrub reinforcement depth of 0.6 m, a tree anchorage depth of 3 m, a grid spacing of 0.4 m, and a top-sparse and bottom-dense tree distribution. The combined slope protection schematic was applied to the Yushi Expressway project in Guizhou, and a strong reinforced slope protection effect was observed.